Historical Application of the Formation of the Three Greatest Islamic Kingdoms of the Middle Ages Based on Augmented Reality - Fatona Kholifatun Nisa'; Rohman Dijaya; Nuril Lutvi Azizah (Universitas Muhammadiyah Sidoarjo, 2022)
The importance of studying Islamic Cultural History (SKI), especially the history of the formation of the three largest medieval Islamic empires, namely that students are able to understand and get many valuable lessons from the events of Islamic revival and struggle, so that they can shape the character of a generation with Islamic values. However, the results of observations made in Private Madrasah Aliyah, Raden Patah, Mojokerto, class X for SKI learning still use the blackboard and in delivering the material it is done by the lecture method. This method resulted in 52% of students being less enthusiastic. Students will be easily sleepy and lazy if only offered learning without innovative media. Then we need a learning method using Augmented Reality (AR) technology, which combines virtual objects and real objects that can be touched and seen so that users can interact directly with these objects. This study aims to create an application as a more effective and interactive learning media in SKI subjects. making this application using Blender 3D as modeling and Unity 3D as application development.